Genders Differentials in Computer Sciences Education: Analysis and Proposal - Xianyang Zeng; Hongxia Zheng (2009 First International Workshop on Education Technology and Computer Science, 2009)
This article discussed the genders differentials in education, especially in computer science course education. Firstly, introduced common sexual difference, pointed out the corresponding outward performance, and the great importance should be pay more attention to. Secondly, after studied the previous results made by others, made a detail investigation and statistics in a university, and more than 76 subjects and 38 thousand student-time were mentioned, to verify the conclusions made. Thirdly, paid more attention to the computer science course education, discussed the genders differentialspsila affect on their scores and choices when met with optional courses. Because of their physiological and psychological difference, boys and girls had made different performance in course scores and made different choice on optional subjects. Fourthly, analyzed the natural, social and cultural causes resulted in these differences, and discussed their specific performance in China. Finally, some proposals had been put forward. Some Legal, economical, social and cultural measures should be taken urgently and effectively.